PENGARUH MICROTEACHING SIMULASI KURIKULUM 2013 TERHADAP PERSEPSI MAHASISWA PADA PEMBELAJARAN KIMIA - Herlina Apriani (Universitas Lambung Mangkurat, 2017)
Abstract. Students' perceptions in chemistry learning are the student’s way to assess and interpret chemistry learning. Students' perceptions in chemistry learning will have an impact on the student’s readiness of teaching as chemistry teacher candidate. This study aims to determine the effect of the Curriculum 2013 microteaching simulation to students' perception in chemistry learning. This research is an experimental research with One Group Pretest-Postest Design. Population in this research is all student of chemistry education UNISKA MAB Banjarmasin follower courses of chemistry learning and teaching strategy. The sample in this study was taken randomly as many as 16 students. The instrument of this study is a questionnaire of perception assessment. The research data was analyzed using SPSS 16.0 for Windows with Wilcoxon test. The results showed that there is effect of Curriculum 2013 microteaching simulation to students' perception in chemistry learning.Keywords: curriculum 2013, microteachng, perception